TECHNOLOGY ACCEPTANCE DAN CONSUMER DECISION MODEL SEBAGAI DASAR PEMBANGUN MODEL NIAT ADOPSI TEKNOLOGI INTERNET DI KALANGAN PENGGUNA INTERNET - Utami, Christina Whidya; Tulipa, Diyah (Jurnal Widya Manajemen & Akuntansi, 2006)
This research explains the model of technological adoption and perception to intention of purchase of the internet consumer in Surabaya. However, consumer behavior that was formed by purchasing intention is threatened by two theories: Technology Acceptance Models (TAM) and Consumer Decision Model (CDM). Technology Acceptance Models predicts the consumer intention to use the information system and technology. While CDM model is used to measure the effectiveness of information media. The results indicate that the models prove the hypotheses. This research indicates that the internet consumer has been using internet as a media to get information, concerning product, hence the online purchasing.